Revision Anterior Cruciate Ligament Reconstruction in Combination With Meniscal and Osteochondral Allograft Transplantation for Complex Knee Injury - Denisse Loya, M.D., M.Sc.; Janina Kaarre, M.D., M.Sc.; Stephen E. Marcaccio, M.D.; Ehab M. Nazzal, M.D.; Christopher J. Como, M.D.; Zachary J. Herman, M.D.; Liane M. Miller, M.D.; Volker Musahl, M.D. (Arthroscopy Techniques)
Revision anterior cruciate ligament reconstruction (ACLR) may present a challenge as a result of several factors, including malpositioned bone tunnels, tunnel osteolysis, and the presence of previous hardware. In addition, concomitant pathology, specifically meniscal and cartilaginous injuries, may be present and should be addressed to minimize the risk of re-rupture. Revision ACLR and treatment of accompanying injuries can be performed either as a 1-stage or 2-stage procedure, yet the latter may increase surgical risk for the patient and extend recovery time. The over-the-top technique serves as a good option for revision ACLR and can be performed with careful consideration of patient-specific anatomy and with proper surgical planning. Therefore, this Technical Note aims to present our 1-stage surgical technique for revision ACLR using over-the-top technique with an Achilles tendon allograft, along with concomitant treatment for meniscal deficiency and a medial femoral condyle chondral defect using meniscal and osteochondral allografts, respectively.